Digital Camp for Student : Workshop Pemrograman Java untuk Siswa SMK Negeri Air Joman Jurusan Rekayasa Perangkat Lunak - Rolly Yesputra; Edi Kurniawan; Nasrun Marpaung; Nuriadi Manurung (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2021)
Abstract: The 4.0 Industrial Revolution can be seen directly from the very rapid progress and changes in information technology in various fields. To be able to keep up with technological developments in the era of the Industrial Revolution 4.0, SMK students must be able to follow the development of information technology, especially programming. With the motto "SMK Can" it is necessary to hold training activities to improve students' abilities. Java programming training is given to students majoring in Software Engineering. The training activity begins with the preparation of Java programming modules and practical activities with the Netbeans IDE to develop applications based on Java Swing and the MariaDB database. This training is carried out in the form of tutorials and workshops that are accompanied directly by the team, so that students can practice the material provided directly and are assisted if there are obstacles in following the modules discussed. The training always begins with a pre-test activity and at the end of the training a post-test will be conducted to test students' understanding. From the results of the pre-test, it is known that the average student does not understand Java programming well. After doing the Post-test, it was found that there was an increase in students' ability to understand Java Swing programming.            Keywords: Java; Java Swing; Programming  Abstrak: Revolusi Industri 4.0 dapat dilihat secara langsung dari kemajuan dan perubahan teknologi informasi yang sangat pesat di berbagai bidang. Untuk dapat mengikuti perkembangan teknologi di era Revolusi Industri 4.0, Siswa SMK harus mampu mengikuti perkembangan teknologi informasi khususnya pemrograman. Dengan motto “SMK Bisa” maka perlu diadakan kegiatan pelatihan untuk meningkatkan kemampuan siswa. Pelatihan pemrograman Java diberikan kepada Mahasiswa jurusan Rekayasa Perangkat Lunak. Kegiatan pelatihan diawali dengan penyusunan modul pemrograman Java dan kegiatan praktikum dengan Netbeans IDE untuk mengembangkan aplikasi berbasis Java Swing dan database MariaDB. Pelatihan ini dilaksanakan dalam bentuk tutorial dan workshop yang didampingi langsung oleh tim, sehingga mahasiswa dapat mempraktekkan materi yang diberikan secara langsung dan dibantu jika ada kendala dalam mengikuti modul yang dibahas. Pelatihan selalu diawali dengan kegiatan pre-test dan di akhir pelatihan akan dilakukan post-test untuk menguji pemahaman siswa. Dari hasil pre-test diketahui bahwa rata-rata siswa belum memahami pemrograman Java dengan baik. Setelah dilakukan Post-test ditemukan adanya peningkatan kemampuan siswa dalam memahami pemrograman Java Swing. Kata kunci: Java; Java Swing; Pemrograman;